Sensação térmica do pedestre - Nakata, Camila Mayumi; Souza, Léa Cristina Lucas de; Faria, João Roberto Gomes de [UNESP] (My University, 2011)
This study has as main objective to identify the complains occurrences about pain in the spine segments, that are related to work standing posture, adopted by the collaborators in the production section of a food industry, in the city of Marília São Paulo state. A descriptive research and studying case was made, using 30 employees as a sample. It was used as methodological procedure, a questionnaire to obtain information on professional and personal data, posture to remain standing, the most uncomfortable postures in the work environment (signed by the form of Ranney, 2000) and pain (pointed out by Corllet and Manenica Diagram, 1980). It was also used the Nordic questionnaire (Kuorioka et al.,1986), validated in the Brazilian culture by Barros e Alexandre (2003) and adapted for the study, the direct evaluation and, a direct observation was made in the production work, a posture analysis using the OWAS Method. It was noticed that the posture of standing up is adopted during work, and 73.3% of the people that was interviewed said that they felt tired in consequence of this posture, especially when associated with trunk twists, trunk inclination and elevation of their arms above their heads. Most complains regarding pain through their bodies, by Corllet e Manenica (1980) pointed to the lumbar region, followed in the dorsal area and legs and in the neck area, shoulders and right thigh. The adapted Nordic questionnaire reveled the lumbar area, in 10 interviewed people (33.3%) as the area mostaffected by musculoskeletal symptoms, next in the dorsal area, with five people interviewed (16.7%) and one of them (3.3%) felt pain in the cervical area, none reported pain in the hips area. The postural analysis was applied using OWAS method, and it was identified the postures that demanded more effort in the four levels of musculoskeletal injuries. As conclusion, the standing up posture and the asymmetric and incorrect movements are related to pain in the spine, mostly in the lumbar area.

Esta pesquisa teve como objetivo identificar as ocorrências de queixas de dores nos segmentos na coluna vertebral, relacionadas com a postura de trabalho em pé, adotada pelos funcionários de uma linha de produção, limitado ao setor Colorido durante as suas atividades laborativas em uma Indústria de Alimentos, na cidade de Marília estado de São Paulo. Foi feita uma pesquisa descritiva de um estudo de caso, com uma amostra composta de 30 funcionários. Utilizou-se como procedimento metodológico, um questionário sobre dados pessoais e profissionais, postura adotada em pé, posturas mais incômodas dentro do ambiente de trabalho (Formulário de Ranney, 2000) o Diagrama de Corllet e Manenica (1980) o questionário Nórdico (Kuorinka et al., 1986), validado na cultura brasileira por Barros e Alexandre (2003) e adaptado para o estudo, a observação direta e o Método Owas. Os resultados apontaram que 73,3% dos entrevistados relatam cansaço de trabalharem “em pé”, principalmente quando há torção e inclinação de tronco e elevação dos braços acima da cabeça. Quanto às dores e desconfortos, indicou as regiões lombares, dorsal, pernas, pescoço, ombros e coxa direita. O Questionário Nórdico apontou a região lombar, como a mais atingida (33,3%), seguida da região dorsal, (16,7%) e da região cervical (3,3%). Concluiu-se que a postura em pé e os movimentos assimétricos têm relação com as dores na coluna vertebral, principalmente na região lombar.
Keywords: Ergonomics; Standing up posture; Back pain; Ergonomia; Postura em pé; Dor na coluna vertebral